Principles of Operation of Three-level Phase Shift Controlled Converter - Kácsor, G.; Špánik, P.; Dudrík, J.; Luft, M.; Szychta, E. (Elektronika ir Elektrotechnika, 2008)
A soft switching resonant DC/DC converter is presented in this paper. The converter is based on a three-level topology with Cool MOS transistors and uses variable frequency control. The principle of operation and some characteristics of the converter are analysed on a simulation model. Ill. 20, bibl. 8 (in English; summaries in English, Russian and Lithuanian).